Studi Tentang Sejarah Kebudayaan Islam Pada Masa Pembaruan - Asmiralda, Febrina; Daulay, Haidar Putra; Sumanti, Sholihah Titin (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to explore further the study of the history of Islamic culture during the reform period. This research uses a qualitative method with a descriptive historical approach. Data was collected through library studies from primary sources such as classical Arabic literature and relevant sources such as books, scientific journals, articles, official documents and other library sources. The results of this research state that the Islamic Development system in the Modern Period is a period that began in 1800 AD when Muslims were aware of their weaknesses and there was an urge to make progress in various fields. Figures who pioneered the Islamic reform movement include; Muhammad bin Abdul Wahab, Syah Waliyullah, Muhammad Ali Pasha, Al-Tahtawi, Jamaludin Al-Afghani, Muhammad Abduh, Rasyid Rida, Sayyid Ahmad Khan, and Sultan Mahmud II. When Islam experienced decline, European nations experienced extraordinary progress in the fields of culture, economy, science and technology. Meanwhile, the condition of the Islamic world was under the influence of European colonialism and imperialism.Keywords: History of Islamic Culture, Period of Reform